2019
DOI: 10.5811/westjem.2019.5.42749
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing the Lag Between Result Availability and Decision-Making in the Emergency Department Using Push Notifications

Abstract: Introduction Emergency department (ED) patient care often hinges on the result of a diagnostic test. Frequently there is a lag time between a test result becoming available for review and physician decision-making or disposition based on that result. We implemented a system that electronically alerts ED providers when test results are available for review via a smartphone- and smartwatch-push notification. We hypothesized this would reduce the time from result to clinical decision-making. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…We examined use at the order-level, but low rates have been previously reported by Koziatek et al, who demonstrated only 2.7% of ED encounters with this similar style of notification. 17 Interestingly our results showed approximately one in six results (17.04%, 391/2,294) had more than one notification request associated with it, implying that multiple providers felt that the result warranted notification and may have been especially important to patient care. Despite a relatively small number of our overall orders having notifications, more than 15% of providers utilized the tool during the study period implying at least some perceived value in it, with a predominance toward use in the hospital setting.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…We examined use at the order-level, but low rates have been previously reported by Koziatek et al, who demonstrated only 2.7% of ED encounters with this similar style of notification. 17 Interestingly our results showed approximately one in six results (17.04%, 391/2,294) had more than one notification request associated with it, implying that multiple providers felt that the result warranted notification and may have been especially important to patient care. Despite a relatively small number of our overall orders having notifications, more than 15% of providers utilized the tool during the study period implying at least some perceived value in it, with a predominance toward use in the hospital setting.…”
Section: Discussionmentioning
confidence: 61%
“…To our knowledge, there is only one study (by Koziatek et al) that examines vendor-based elective electronic notifications on patient care, and it is limited to the ED setting. 17 Even less is known about what motivates a provider to be notified at the time of elective notification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive number of publications have also examined the impact of alert notifications on critical laboratory results. Although sometimes contradictory or pointing out the risk of alert fatigue potentially slowing the response to these alerts and harmful to the patient [ 43 , 44 , 45 ], they mostly show a significant reduction in time lag between laboratory result availability and decision making, a high degree of clinician approval, and a beneficial impact on patient care [ 25 , 46 , 47 , 48 , 49 ]. During 2018, there were an estimated 130 million ED visits in the USA.…”
Section: Discussionmentioning
confidence: 99%